Potentiometric Determination of Chlorate Impurities in Hypochlorite Solutions - Dmitry V. Girenko; Al’ona A. Gyrenko; Nikolai V. Nikolenko (International Journal of Analytical Chemistry)
The method of iodometric determination of chlorates impurities in sodium hypochlorite solutions for medical and veterinary purposes was developed. This method does not require sophisticated equipment and can be implemented directly where the solutions are used. The method is based on the different rates of interaction of ClO- and ClO3- with iodide ions depending on the acidity of the medium. We have shown that blank titration is advisable to improve the accuracy of the determination of low concentrations of chlorates in the matrix of hypochlorite which is present in excess since in this case possible systematic errors due to the presence of oxidizing impurities in the reagents are prevented. To quantify the low concentrations of chlorates, we proposed to remove 85-95% of hypochlorite ions by means of reducing their excess with sodium sulfite at pH 10.5. The solution of sodium sulfite does not require standardization before each analysis in the proposed procedure. The possibility of quantitative determination of chlorate impurities in the range of 2-50 mg/L in the presence of 50-500–fold excess of sodium hypochlorite with an error of 5% has been proved. The expanded uncertainty of chlorate determination did not exceed 0.6 mg/L.